Modified carboxylated polysaccharide compositions and uses of said compositions

By introducing monovalent and divalent cations into hydroxymethylcellulose (CMC) to form functionalized water-soluble salts, the problem of difficulty in maintaining water solubility and biodegradability in the prior art is solved, and performance improvements in various applications are achieved.

JP2025512959APending Publication Date: 2025-04-22ISP INVESTMENTS LLC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024559182
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-05
Filing Date
2023-01-31
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously introduce multivalent metal ions into hydroxymethylcellulose (CMC) in maintaining water solubility and biodegradability, affecting its performance.

Method used

By introducing at least one monovalent cation (M+) and at least one divalent cation (M++) into hydroxymethylcellulose (CMC), a functionalized water-soluble salt is formed, maintaining its water-soluble and biodegradable.

Benefits of technology

It has achieved the introduction of multivalent metal ions without affecting water solubility and biodegradability, which improves the performance of CMC and is suitable for a variety of applications, such as adhesives, tooth stabilizers and toothpastes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025512959000001_ABST
    Figure 2025512959000001_ABST
Patent Text Reader

Abstract

Modified carboxylated polysaccharides, more particularly those containing at least one monovalent cation (M + ) and at least one divalent cation (M ++ A modified carboxymethyl cellulose (CMC) functionalized with at least one monovalent cation (M + ) and at least one divalent cation (M ++ Further disclosed is a mucoadhesive composition comprising a modified carboxymethylcellulose (CMC) functionalized with carboxymethylcellulose (CMC). Further disclosed is the use of the mucoadhesive composition in denture adhesives and toothpaste type compositions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to modified carboxylated polysaccharides, in particular modified carboxymethylcellulose (CMC), more particularly modified carboxymethylcellulose (CMC) containing at least one monovalent cation (M + ) and at least one divalent cation (M ++ The present invention relates to a water-soluble salt of carboxymethylcellulose (CMC) functionalized with carboxymethylcellulose (CMC), a method for preparing said water-soluble salt, and uses of said water-soluble salt. [Background technology]

[0002] Carboxylated polysaccharides such as carboxymethylcellulose (CMC), carboxymethyl inulin, carboxymethyl guar or carboxymethyl starch are long chain polymers with solubility properties that depend on the average chain length, degree of polymerization (DP) and degree of substitution (DS). 2 , C 3 and C 6 The average amount of hydroxyl groups replaced by sodium carboxyethyl ether groups in CMC is represented by the DS value. As the molecular weight increases, the viscosity of the CMC solution also increases. Sodium carboxymethylcellulose (NaCMC) is an anionic water-soluble polyelectrolyte that has numerous applications in the food, pharmaceutical, personal care, home care, cosmetics, paper and other industries. Sodium CMC is inherently biodegradable or can be easily biodegraded at a DS value of 0.7 or less. When the carboxymethyl groups of CMC are replaced by cations other than sodium ions, such as divalent cations such as calcium ions, magnesium ions, zinc ions, tin ions, etc., various changes in properties are commonly observed, including but not limited to a decrease in viscosity and water solubility.

[0003] The paper "Effect of mono- and di-valent salts on the properties of carboxymethyl cellulose hydrogel under irradiation technique" published in International Journal of Chemical Sciences, 627-634, 10(2), January 2012, discloses an investigation into the swelling properties and gelation rate of CMC hydrogels prepared by gamma radiation in the presence of monovalent and divalent salts (NaCl and CaCl2).

[0004] U.S. Patent Application Publication No. 2005 / 0032940 (assigned to HealthTech Corporation) discloses an adhesive-type denture fixative comprising a water-soluble polymer containing 0.1-20% by weight calcium sulfate and 3-60% by weight sodium carboxymethylcellulose to react with the calcium sulfate upon contact with an aqueous component to form a gel. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] US Patent Application Publication No. 2005 / 0032940 [Non-patent literature]

[0006] [Non-Patent Document 1] "Effect of mono- and di-valent salts on the properties of carboxymethyl cellulose hydrogel under irradiation technique" published in International Journal of Chemical Sciences, 627~634, 10(2), January 2012 Summary of the Invention [Problem to be solved by the invention]

[0007] Herein, the inventors describe high molecular weight modified polysaccharides, in particular modified carboxymethylcelluloses, which have been modified by the addition of at least one monovalent cation (M + ) and at least one divalent cation (M ++ This application discloses a modified carboxymethyl cellulose functionalized with [Means for solving the problem]

[0008] The first aspect of the present application is a modified carboxylated polysaccharide, in particular a modified carboxymethylcellulose (CMC), which is characterized by the incorporation of at least one monovalent cation (M + ) and at least one divalent cation (M ++ The present invention provides a modified carboxymethylcellulose (CMC), which is a water-soluble salt of carboxymethylcellulose (CMC) functionalized with carboxymethylcellulose (CMC).

[0009] In another aspect, the present application relates to a compound having the structure (I): [ka] (In the formula, M + is a monovalent cation selected from the group consisting of sodium ions, potassium ions, and lithium ions; M ++ is a divalent cation selected from the group consisting of calcium, magnesium, zinc, tin, copper, and combinations thereof, n=2 to 500, and M + =0.1~10wt% and M ++ = 0.1 to 10 wt %.

[0010] In another embodiment, the functionalized carboxymethylcellulose is (i) carboxymethylcellulose calcium sodium (Na + -Ca ++-CMC), (ii) sodium magnesium carboxymethylcellulose (Na + -Mg ++ -CMC), (iii) sodium carboxymethylcellulose zinc (Na + -Zn ++ -CMC), (iv) Carboxymethylcellulose zinc calcium sodium (Na + -Ca ++ -Zn ++ -CMC), (v) Carboxymethylcellulose magnesium calcium sodium (Na + -Ca ++ -Mg ++ -CMC), (vi) Carboxymethylcellulose zinc magnesium sodium (Na + -Mg ++ -Zn ++ -CMC), (vii) Sodium carboxymethylcellulose tin (Na + -Sn ++ -CMC), (viii) carboxymethylcellulose tin calcium sodium (Na + -Ca ++ -Sn ++ -CMC), (ix) Sodium tin magnesium carboxymethylcellulose (Na + -Mg ++ -Sn ++ -CMC) or (x) Carboxymethylcellulose tin zinc sodium (Na + -Zn ++ -Sn ++ -CMC).

[0011] In another aspect, the present application provides a mucoadhesive composition comprising: (i) (a) at least one monovalent cation (M + ) and at least one divalent cation (M ++ or (b) (b1) a water-soluble salt of 0.1 wt % to 60 wt % of carboxymethylcellulose (CMC) functionalized with at least one monovalent cation (M + ) and at least one divalent cation (M ++(b2) a water-soluble salt of carboxymethylcellulose (CMC) functionalized with at least one monovalent cation (M + ) functionalized with a water-soluble salt of carboxymethylcellulose (CMC) at 0.1 wt % to 60 wt %, and (ii) a substantially alternating monomer structure of C 1 ~C 4 The present invention provides a mucoadhesive composition comprising: (i) 0.1 wt% to 60 wt% of a maleic acid or maleic anhydride copolymer of an alkyl vinyl ether and maleic acid or maleic anhydride monomer, wherein 50 to 90 wt% of the acid moieties in the polymer have been converted to a metal or mixed salt; and (ii) 0.1 wt% to 80 wt% of at least one further ingredient.

[0012] In another aspect, the present application provides a denture adhesive type composition comprising: (i) (a) at least one monovalent cation (M + ) and at least one divalent cation (M ++ or (b) (b1) a water-soluble salt of 0.1 wt % to 60 wt % of carboxymethylcellulose (CMC) functionalized with at least one monovalent cation (M + ) and at least one divalent cation (M ++ (b2) a water-soluble salt of carboxymethylcellulose (CMC) functionalized with at least one monovalent cation (M + ) functionalized with a water-soluble salt of carboxymethylcellulose (CMC) at 0.1 wt % to 60 wt %, and (ii) a substantially alternating monomer structure of C 1 ~C 4 A denture fixative type composition is provided comprising: (i) 0.1 wt % to 60 wt % of a maleic acid or maleic anhydride copolymer of an alkyl vinyl ether and maleic acid or maleic anhydride monomer, wherein 50 to 90 wt % of the acid moieties of the polymer have been converted to a metal or mixed salt; and (ii) 0.1 wt % to 80 wt % of at least one further ingredient.

[0013] In another aspect, the present application provides a toothpaste-type composition comprising: (i) (a) at least one monovalent cation (M + ) and at least one divalent cation (M ++ or (b) (b1) 0.1 wt % to 20 wt % water-soluble salt of carboxymethyl cellulose (CMC) functionalized with at least one monovalent cation (M + ) and at least one divalent cation (M ++ (b2) a water-soluble salt of carboxymethylcellulose (CMC) functionalized with at least one monovalent cation (M + (ii) 0.1 wt% to 60 wt% of an orally acceptable solvent or carrier selected from water, glycerin, polyethylene glycol, polypropylene glycol, sorbitol, PEG, ethylene oxide-propylene oxide polymers, or combinations thereof; and (iii) a mixture of, but not limited to, maleic anhydride, maleic acid, C 1 ~C 4% to 20 wt. % of an orally acceptable polymer of monomers comprising alkyl vinyl ether, alkylene oxide, alkyl lactam, triglyceride, animal or vegetable oil, or combinations thereof; and (iv) an active agent selected from the group including, but not limited to, abrasives, antibacterial agents, antiplaque agents, antitartar agents, biofilm inhibitors, antihypersensitivity agents, antigingivitis agents, fluoride delivering compounds, dispersants, deposition agents, etc. and 0.1-80 wt % of further ingredients comprising a surfactant selected from the group ...

[0014] In another aspect, the present application provides a method for the preparation of a compound comprising: (i) at least one monovalent (M + ) a carboxymethylcellulose salt; and (ii) one or more divalent (M ++ ) Metal salts An ion exchange process comprising the reaction of divalent (M ++ ) Salt, M ++ Chloride or M ++ Sulfate or M ++ carbonates, and M in the ion-exchange product CMC + M ++ The present invention provides a functionalized carboxymethyl cellulose acetate obtained by an ion exchange process, in which the weight ratio of carboxymethyl cellulose acetate to carboxymethyl cellulose acetate is about 1:75 to about 75:1.

[0015] In yet another aspect, the present application provides a method for the preparation of a monovalent cation-divalent cation (M + -M ++(i) (a) a method for preparing M-carboxymethylcellulose comprising the steps of: ++ Chloride, M ++ Sulfate or M ++ Carbonates and (b) C 2 ~C 4 (ii) preparing an aqueous solution of sodium carboxymethylcellulose (M + (iii) filtering the product of step (ii) to obtain a wet cake; (iv) stirring the wet cake of step (iii) in a hydroalcoholic solution for at least 30 minutes; and (v) repeating step (iv) at least three times to obtain M. + -M ++ (vi) drying the wet cake of step (v) at 50-70° C. for at least 15-30 minutes in a fluid bed dryer to obtain a dried M + -M ++ (vii) grinding the product of step (vi) to obtain carboxymethylcellulose; + -M ++ - obtaining a dry powder of carboxymethyl cellulose.

[0016] In addition to the advantages and objectives of the present disclosure described above, one or more explanations regarding the present disclosure briefly summarized can be added by referring to the specific embodiments of the present disclosure shown in the attached drawings. These drawings form a part of this specification. However, it should be noted that the attached drawings illustrate preferred embodiments of the present disclosure and therefore do not limit the scope of the present disclosure. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 shows the adhesion performance of sodium-magnesium-CMC (Na+-Mg++-CMC) containing denture adhesive type formulations (DA29-31). [Diagram 2]FIG. 1 shows total deposition of sodium-magnesium-CMC (Na+-Mg++-CMC) containing denture adhesive type formulations (DA29-31). [Diagram 3] FIG. 1 shows the adhesion performance of sodium-calcium-CMC (Na+-Ca++-CMC) containing denture adhesive type formulations (DA35-38). [Figure 4] FIG. 1 shows the total deposition of sodium-calcium-CMC (Na+-Ca++-CMC) containing denture adhesive type formulations (DA35-38). [Diagram 5] FIG. 1 shows the adhesion performance of sodium-calcium-CMC (Na+-Ca++-CMC) containing denture adhesive type formulation (DA39-42). [Figure 6] FIG. 1 shows the total deposition of a sodium-calcium-CMC (Na+-Ca++-CMC) containing denture adhesive type formulation (DA39-42). [Figure 7] FIG. 1 shows the adhesion performance of sodium-calcium-CMC (Na+-Ca++-CMC) containing denture adhesive type formulation (DA43-46). [Figure 8] FIG. 1 shows the total deposition of sodium-calcium-CMC (Na+-Ca++-CMC) containing denture adhesive type formulation (DA43-46). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Before describing in detail at least one aspect of the disclosed and / or claimed inventive concept(s), it is to be understood that application of the disclosed and / or claimed inventive concept(s) is not limited to the details of construction and arrangement of the components or steps or methods set forth in the following description or illustrated in the drawings. The disclosed and / or claimed inventive concept(s) is / are capable of other embodiments or of being practiced or carried out in various ways. Moreover, it is to be understood that the phraseology and terminology employed herein is for the purpose of description and should not be construed as limiting.

[0019] As utilized in accordance with the present disclosure, the following terms, unless otherwise indicated, shall be understood to have the following meanings.

[0020] Unless otherwise specified herein, technical terms used in connection with the inventive concepts disclosed and / or claimed herein shall have the meanings commonly understood by those of ordinary skill in the art. Further, unless otherwise required by context, singular terms shall include the plural and plural terms shall include the singular.

[0021] The singular forms "a," "an," and "said" include the plural forms unless the context clearly dictates otherwise or is clearly implied by the referenced context. The terms "comprising" and "including" include more restrictive assertions such as "consisting essentially of" and "consisting of."

[0022] In the following detailed description, except in some useful examples or where otherwise indicated, the numerical values ​​expressing amounts of ingredients used in the specification and claims, for example, should be understood to be modified in all instances by the term "about." The numerical parameters set forth in the specification and appended claims are approximations that may vary depending upon the desired properties sought to be obtained in the practice of the invention.

[0023] All percentages, parts, ratios and proportions used herein are by weight of the total composition unless otherwise specified. All weights referred to above pertaining to listed ingredients are based on active level and therefore do not include solvents or by-products that may be included in commercially available materials unless otherwise specified.

[0024] All publications, articles, papers, patents, patent publications, and other references cited herein are incorporated herein in their entirety for all purposes to the extent not inconsistent with the disclosure herein.

[0025] Use of the term "at least one" is understood to include 1 and any amount greater than 1, including but not limited to 1, 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 100, etc. The term "at least one" can expand to 100 or 1000 or more depending on the term to which the term "at least one" is attached. Furthermore, the amount of 100 / 1000 should not be considered as limiting, as lower or higher limits may provide satisfactory results.

[0026] As used in this specification, the words "comprising" (and any form of comprising, such as "comprising" and "comprising"), "having" (and any form of comprising, such as "had" and "having"), "including" (and any form of comprising, such as "included" and "comprising") or "containing" (and any form of containing, such as "contained" and "containing") are intended to be inclusive or open-ended and do not exclude additional, unrecited elements or method steps.

[0027] As used herein, the term "degree of substitution" or "DS" refers to the average number of substituted hydroxyl groups per anhydroglucose unit.

[0028] As used herein, the term "monovalent cation" refers to a cation with a valence of one. Thus, the term "divalent cation" refers to a cation with a valence of two. The monovalent cation is selected from the group consisting of sodium, potassium, and lithium. Most preferably, the monovalent cation is sodium. The divalent cation is selected from the group consisting of calcium, magnesium, zinc, tin, copper, and combinations thereof. More preferably, the divalent cation is calcium, magnesium, zinc, and combinations thereof.

[0029] In one non-limiting embodiment, the present application provides a method for the preparation of a medicament comprising administering to a subject a medicament the steps of: +) and at least one divalent cation (M ++ The polysaccharide is selected from the group including carboxymethyl cellulose (CMC), carboxymethyl inulin, carboxymethyl guar and carboxymethyl starch.

[0030] As used herein, the term "functionalized" with respect to "carboxylated polysaccharides," and in particular the carboxymethylcellulose of the present application, refers to the presence of monovalent cations and one or more divalent cations in the polysaccharide or carboxymethylcellulose. Various monovalent and divalent cations can be introduced into the carboxymethylcellulose by one or more functionalization reactions known to those skilled in the art. Non-limiting examples of functionalization reactions include: (i) the introduction of at least one monovalent (M + ) a carboxymethylcellulose salt; and (ii) one or more divalent (M ++ ion exchange process involving reaction with a divalent (M ++ ) Salt, M ++ Chloride or M ++ Sulfate or M ++ carbonates, and M in the final ion-exchanged carboxymethylcellulose (CMC) polymer + M ++ to about 1:70 to about 70:1 by weight.

[0031] Thus, the functionalized carboxylated polysaccharides are used in a variety of oral care compositions selected from mucoadhesive compositions, toothpaste / dentifrice type compositions, oral treatment compositions, mouthrinses and denture adhesive type compositions.

[0032] In another non-limiting embodiment, the present application provides a functionalized carboxylated polysaccharide, i.e., a carboxylated polysaccharide having at least one monovalent cation (M + ) and at least one divalent cation (M ++ The present invention provides a water-soluble salt of carboxymethyl cellulose (CMC) functionalized with

[0033] The term "functionalized carboxymethylcellulose" refers to carboxymethylcellulose that is functionalized with at least one monovalent cation (M + ) and at least one divalent cation (M ++ ), wherein the monovalent cation is selected from the group consisting of sodium, potassium and lithium, and the divalent cation is selected from the group consisting of calcium, magnesium, zinc, tin, copper and combinations thereof.

[0034] The carboxymethyl cellulose functionalized with at least one monovalent cation and at least one divalent cation has the structure (I): [ka] CMCs functionalized with monovalent and divalent cations (In the formula, M + is a monovalent cation selected from the group consisting of sodium ions, potassium ions, and lithium ions; M ++ is a divalent cation selected from the group consisting of calcium, magnesium, zinc, tin, copper, and combinations thereof; n ≧ 2 to n ≦ 2000, and M for carboxymethyl cellulose + =0.1~10wt% and M ++ =0.1 to 7.5 wt%.

[0035] In another non-limiting embodiment, the present application discloses a functionalized carboxymethylcellulose containing 0.1-10 wt% monovalent cations and 0.1-10 wt% one or more divalent cations. In another embodiment, the divalent cations are present in an amount of about 0.2-7.5 wt% based on the total CMC content.

[0036] In another non-limiting embodiment, the present application provides a method for treating a univalent cation (M + ) divalent cations (M ++In some embodiments, the weight ratio of M to M is about 1:75 to about 75:1 in the final functionalized CMC polymer. + M ++ to about 1:3 to about 3:1, or about 1:5 to about 5:1, or about 1:10 to about 10:1, or about 1:20 to about 20:1, or about 1:30 to about 30:1, or about 1:40 to about 40:1, or about 1:50 to about 50:1, or about 1:60 to about 60:1, or about 1:70 to about 70:1 in the final functionalized CMC polymer. + M ++ The preferred weight ratio of the monovalent cations to the divalent cations is about 1:3 to about 3:1, or about 1:5 to about 5:1, or about 1:10 to about 10:1. In a preferred embodiment, the monovalent cations and the divalent cations are present in the final functionalized CMC polymer in a weight ratio of 75 to 1:1 to 75.

[0037] In another non-limiting embodiment, the present application provides a modified carboxymethyl cellulose (CMC), the CMC optionally comprising at least one monovalent cation (M + The modified carboxymethyl cellulose (CMC) is further combined with a functionalized carboxymethyl cellulose (CMC) having at least one monovalent cation. Thus, the functionalized carboxymethyl cellulose having at least one monovalent cation is represented by the structure of (II): [ka] CMC functionalized with monovalent cations (In the formula, M + is a monovalent cation selected from the group consisting of sodium ions, potassium ions, and lithium ions, n≧2 to n≦2000, and M + =0.1~10wt%.

[0038] In another non-limiting embodiment, the present application provides a method for treating a pulmonary artery disease comprising administering to a patient a pulmonary artery disease comprising administering to the ... + ) and at least a divalent cation (M++ This invention discloses a functionalized biodegradable carboxymethylcellulose (CMC) containing a monovalent cation (M + ) is selected from the group consisting of sodium, potassium and lithium. ++ ) is selected from the group consisting of calcium, magnesium, zinc, copper, tin, and combinations thereof. Additionally, the functionalized carboxymethylcellulose (CMC) can be in dry powder form.

[0039] In another non-limiting embodiment, the functionalized carboxymethylcellulose has a degree of substitution in the range of about 0.4 to about 0.5, or in the range of about 0.5 to about 0.6, or in the range of about 0.6 to about 0.7, or in the range of about 0.7 to about 0.8, or in the range of about 0.8 to about 0.9, or in the range of about 0.9 to about 1.0, or in the range of about 1.0 to about 1.1, or in the range of about 1.1 to about 1.2. In a preferred embodiment, the degree of substitution is in the range of about 0.4 to about 0.7. In another preferred embodiment, the modified cellulose has a DS of about 0.4 to about 1.2.

[0040] In another non-limiting embodiment, the functionalized carboxymethylcellulose has a low-medium molecular weight range or a medium-high molecular weight range. The low-medium molecular weight range refers to a functionalized carboxymethylcellulose (CMC) having a weight average molecular weight of about 2,000 to about 200,000 Daltons. Similarly, the medium-high molecular weight range refers to a functionalized carboxymethylcellulose (CMC) having a weight average molecular weight of about 200,000 to about 2,000,000 Daltons.

[0041] In some embodiments, the average molecular weight is in the range of about 2000 to about 2,000,000 daltons. In some embodiments, the average molecular weight is in the range of about 10,000 to about 15,000 daltons, or about 15,000 to about 20,000 daltons, or about 20,000 to about 300,000, or about 30,000 to about 40,000 daltons, or about 40,000 to about 50,000 daltons, or about 50,000 to about 60,000 daltons, or about 60,000 to about 70,000 daltons, or about 70,000 to about 80,000 daltons. In some embodiments, the average molecular weight is in the range of about 80,000 to about 90,000 daltons, or in the range of about 90,000 to about 100,000 daltons, or in the range of about 100,000 to about 200,000 daltons, or in the range of about 200,000 to about 300,000 daltons, or in the range of about 300,000 to about 400,000 daltons, or in the range of about 400,000 to 500,000 daltons. or in the range of about 500,000 to 600,000 daltons, or in the range of about 600,000 to 700,000 daltons, or in the range of about 700,000 to 800,000 daltons, or in the range of about 800,000 to 900,000 daltons, or in the range of about 900,000 to 1,000,000 daltons, or in the range of about 1,000,000 to 1,100,000 daltons. In a preferred embodiment, the functionalized carboxymethylcellulose has a weight average molecular weight in the range of 2000 to 1,500,000 daltons. In another preferred embodiment, the functionalized carboxymethylcellulose has a weight average molecular weight in the range of 80,000 to 1,300,000 daltons.

[0042] Therefore, the functionalized carboxymethyl cellulose (CMC) is biodegradable.

[0043] In another non-limiting embodiment, the functionalized water soluble carboxymethylcellulose is (i) carboxymethylcellulose calcium sodium (Na + -Ca ++ -CMC), (ii) sodium magnesium carboxymethylcellulose (Na + -Mg ++-CMC), (iii) sodium carboxymethylcellulose zinc (Na + -Zn ++ -CMC), (iv) Carboxymethylcellulose zinc calcium sodium (Na + -Ca ++ -Zn ++ -CMC), (v) Carboxymethylcellulose magnesium calcium sodium (Na + -Ca ++ -Mg ++ -CMC), (vi) Carboxymethylcellulose zinc magnesium sodium (Na + -Mg ++ -Zn ++ -CMC), (vii) Sodium carboxymethylcellulose tin (Na + -Sn ++ -CMC, (viii) carboxymethylcellulose tin calcium sodium (Na + -Ca ++ -Sn ++ -CMC), (ix) Sodium tin magnesium carboxymethylcellulose (Na + -Mg ++ -Sn ++ -CMC) or (x) Carboxymethylcellulose tin zinc sodium (Na + -Zn ++ -Sn ++ -CMC). Furthermore, sodium carboxymethylcellulose (Na + -CMC) can be combined with at least one functionalized carboxymethylcellulose (CMC) selected from the combinations of monovalent and divalent salts of CMC described herein above.

[0044] In another non-limiting embodiment, the functionalized water soluble carboxymethylcellulose is selected from the group consisting of (i) calcium potassium carboxymethylcellulose (K + -Ca ++ -CMC), (ii) magnesium potassium carboxymethylcellulose (K + -Mg ++-CMC), (iii) potassium carboxymethylcellulose zinc (K + -Zn ++ -CMC), (iv) potassium carboxymethylcellulose tin (K + -Sn ++ -CMC), (v) Carboxymethylcellulose zinc calcium potassium (K + -Ca ++ -Zn ++ -CMC), (vi) Carboxymethylcellulose magnesium calcium potassium (K + -Ca ++ -Mg ++ -CMC), (vii) carboxymethylcellulose tin calcium potassium (K + -Ca ++ -Sn ++ -CMC), (viii) Carboxymethylcellulose zinc magnesium potassium (K + -Mg ++ -Zn ++ -CMC), (ix) carboxymethylcellulose tin magnesium potassium (K + -Mg ++ -Sn ++ -CMC) and (x) Carboxymethylcellulose tin zinc potassium (K + -Zn ++ -Sn ++ -CMC).

[0045] In another non-limiting embodiment, the functionalized water soluble carboxymethylcellulose is (i) carboxymethylcellulose calcium lithium (Li + -Ca ++ -CMC), (ii) carboxymethylcellulose magnesium lithium (Li + -Mg ++ -CMC), (iii) Lithium carboxymethylcellulose zinc (Li + -Zn ++ -CMC), (iv) carboxymethylcellulose tin lithium (Li + -Sn ++-CMC), (v) Carboxymethylcellulose zinc calcium lithium (Li + -Ca ++ -Zn ++ -CMC), (vi) Carboxymethylcellulose magnesium calcium lithium (Li + -Ca ++ -Mg ++ -CMC), (vii) Carboxymethylcellulose tin calcium lithium (Li + -Ca ++ -Sn ++ -CMC), (viii) Carboxymethylcellulose zinc magnesium lithium (Li + -Mg ++ -Zn ++ -CMC), (ix) Carboxymethylcellulose tin magnesium lithium -(Li + -Mg ++ -Sn ++ -CMC) and (x) Carboxymethylcellulose tin zinc lithium (Li + -Zn ++ -Sn ++ -CMC).

[0046] In another non-limiting embodiment, the functionalized CMC is carboxymethylcellulose calcium sodium (Na + -Ca ++ -CMC) or sodium magnesium carboxymethylcellulose (Na + -Mg ++ -CMC) or sodium carboxymethylcellulose zinc (Na + -Zn ++ -CMC).

[0047] In another non-limiting embodiment, the functionalized carboxymethylcellulose (CMC) is (i) sodium carboxymethylcellulose (Na + -CMC), and (ii) (a) carboxymethylcellulose calcium sodium (Na + -Ca ++ -CMC) or (b) sodium magnesium carboxymethylcellulose (Na+ -Mg ++ -CMC) or (c) sodium carboxymethylcellulose zinc (Na + -Zn ++ -CMC).

[0048] The functionalized carboxymethylcellulose may be in the form of microcrystals, granules, a powder or a solution.

[0049] In other non-limiting embodiments, the functionalized carboxymethylcellulose (CMC) is used in oral care compositions, pharmaceutical compositions, home care compositions, industrial compositions, skin care compositions, food and dietary supplement compositions, coating compositions, and oil and energy industry compositions.

[0050] Functionalized carboxymethylcellulose (CMC) is used in oral care compositions selected from mucoadhesive compositions, toothpaste / dentifrice type compositions, oral treatment compositions, mouthrinse compositions and denture adhesive type compositions.

[0051] In another non-limiting embodiment, the present application provides a mucoadhesive composition comprising: (a) at least one monovalent cation (M + ) and at least one divalent cation (M ++ or (b) (b1) a water-soluble salt of 0.1 wt % to 60 wt % of carboxymethylcellulose (CMC) functionalized with one monovalent cation (M + ) and at least one divalent cation (M ++ (b2) a water-soluble salt of carboxymethylcellulose (CMC) functionalized with at least one monovalent cation (M + ) functionalized with a water-soluble salt of carboxymethylcellulose (CMC) at 0.1 wt % to 60 wt %, and (ii) a substantially alternating monomer structure of C 1 ~C 4The present invention provides a mucoadhesive composition comprising: (i) 0.1 wt% to 60 wt% of a maleic acid or maleic anhydride copolymer of an alkyl vinyl ether and maleic acid or maleic anhydride monomer, wherein 50 to 90 wt% of the acid moieties in the polymer have been converted to a metal or mixed salt; and (ii) 0.1 wt% to 80 wt% of at least one further ingredient.

[0052] In another embodiment, the present application provides a composition comprising from about 0.1 wt% to about 1 wt%, or from about 1 wt% to about 2.5 wt%, or from about 2.5 wt% to about 5 wt%, or from about 5 wt% to about 10 wt%, or from about 10 wt% to about 15 wt%, or from about 15 wt% to about 20 wt%, or from about 20 wt% to about 25 wt%, or from about 25 wt% to about 30 wt%, or from about 30 wt% to about 35 wt%, or from about 35 wt% to about 40 wt%, or from about 40 wt% to about 45 wt%, or from about 45 wt% to about 50 wt%, based on the total weight of the mucoadhesive composition. % to about 50 wt%, or about 50 wt% to about 55 wt%, or about 55 wt% to about 60 wt%, or about 60 wt% to about 65 wt%, or about 65 wt% to about 70 wt%, or about 70 wt% to about 75 wt%, or about 75 wt% to about 80 wt%, or about 80 wt% to about 85 wt%, or 85 wt% to about 90 wt%, or 90 wt% to about 95 wt%, or 95 wt% to about 99.9 wt%.

[0053] The mucoadhesive composition comprises a functionalized water-soluble carboxymethylcellulose (CMC) having a degree of substitution in the range of 0.4 to 1.2. The biodegradable functionalized water-soluble carboxymethylcellulose (CMC) has a degree of substitution in the range of 0.4 to 0.7.

[0054] The functionalized carboxymethyl cellulose has a weight average molecular weight in the range of 2000 to 2,000,000 Daltons.

[0055] In another non-limiting embodiment, the mucoadhesive composition comprises a substantially alternating monomer structure of C 1 ~C 4Maleic acid or maleic anhydride copolymers of alkyl vinyl ethers and maleic acid or maleic anhydride monomers, wherein 50-90 wt. % of the acid moieties in the polymer are substituted with at least one monovalent cation (M + ) and at least one divalent cation (M ++ ) or mixed salts thereof. Thus, maleic acid or maleic anhydride copolymers can be prepared by converting about 50 mole percent maleic acid or maleic anhydride and about 50 mole percent C to a salt or mixed salt thereof at about 50-150° C. in the presence of a free radical initiator in a solvent or solventless process. 1 ~C 4 Maleic acid or maleic anhydride having a predetermined weight average molecular weight of about 500,000 to 3,000,000 and C produced by copolymerizing maleic acid or maleic anhydride with an alkyl vinyl ether to produce a uniform fine powder substantially free of residual maleic anhydride. 1 ~C 4 Contains alkyl vinyl ether.

[0056] Maleic acid or maleic anhydride and C 1 ~C 4The alkyl vinyl ether is a methyl vinyl ether-maleic acid copolymer or a methyl vinyl ether-maleic anhydride copolymer having a number average molecular weight between about 50,000 and about 500,000, in which about 50 to about 100 wt% of the carboxyl units in the polymer are converted to a mixture of metal salts selected from the group consisting of calcium, sodium, strontium, zinc, magnesium, iron, boron, aluminum, potassium, vanadium, chromium, manganese, nickel, copper, yttrium, titanium, and mixtures thereof. Preferably, the methyl vinyl ether-maleic acid or methyl vinyl ether-maleic anhydride copolymer salt has a specific viscosity of about 2.5 to 5.0 when measured at 25° C. as a 1% w / v solution in methyl ethyl ketone (MEK) solution. The methyl vinyl ether-maleic acid or methyl vinyl ether-maleic anhydride copolymer or a salt of this copolymer constitutes about 10 to about 66 wt % of the mucoadhesive composition. Preferably, the methyl vinyl ether-maleic acid copolymer or methyl vinyl ether-maleic anhydride copolymer has a weight average molecular weight of about 700,000 to about 3,000,000.

[0057] In another embodiment, the mucoadhesive composition provides further ingredients selected from the group consisting of abrasives, anti-caking agents, anti-fungals, anti-bacterial agents, anesthetics, antioxidants, antibiotics, anti-inflammatory agents, binders, buffers, colourants, cooling agents, dentin desensitising agents, dispersants, enzymes, foaming agents, flavours, fillers, fragrances, gelling agents, humectants, hydrophobic carriers, hydrophilic oil-free ingredients, preservatives, pigments, plasticisers, analgesics, sweeteners, thickeners, viscosity modifiers, excipients, surfactants, stabilizers, sensates and mixtures thereof. Preferably, the further ingredients are selected from petrolatum, mineral oil, olive oil, vegetable oil, silicones, glycerin, polyethylene glycol, propylene glycol, polypropylene glycol, poly(ethylene oxide-propylene oxide) copolymers, diethylene glycol, triethylene glycol, sorbitol, water and mixtures thereof.

[0058] In other non-limiting embodiments, the mucoadhesive composition is a buccal composition, oral composition, vaginal composition, nasal composition, rectal composition, ophthalmic composition, sublingual composition, palatal composition, and denture adhesive type composition. The mucoadhesive composition is formulated into an ointment, lotion, liquid, solid, semisolid, emulsion, powder, paste, dispersion, gel, patch, aerosol, or spray.

[0059] In another non-limiting embodiment, the present application provides a denture adhesive type composition comprising: (i) (a) at least one monovalent cation (M + ) and at least one divalent cation (M ++ or (b) (b1) a water-soluble salt of 0.1 wt % to 60 wt % of carboxymethylcellulose (CMC) functionalized with one monovalent cation (M + ) and at least one divalent cation (M ++ (b2) a water-soluble salt of carboxymethylcellulose (CMC) functionalized with at least one monovalent cation (M + ) functionalized with a water-soluble salt of carboxymethylcellulose (CMC) at 0.1 wt % to 60 wt %, and (ii) a substantially alternating monomer structure of C 1 ~C 4 A denture fixative type composition is provided, comprising: 0.1 wt% to 60 wt% of a maleic acid or maleic anhydride copolymer of an alkyl vinyl ether and maleic acid or maleic anhydride monomer, wherein 50 to 90 wt% of the acid moieties in the polymer are converted to a metal salt or mixed salt; and (iii) 0.1 wt% to 80 wt% of at least one further ingredient. The denture fixative type composition comprises a functionalized water-soluble carboxymethylcellulose (CMC) having a degree of substitution in the range of 0.4 to 0.7. Preferably, the denture fixative type composition comprises a functionalized water-soluble carboxymethylcellulose (CMC) having a degree of substitution in the range of 0.4 to 1.2.

[0060] The functionalized carboxymethyl cellulose has a weight average molecular weight in the range of 2000 to 2,000,000 Daltons. 1 ~C 4 Maleic acid or maleic anhydride copolymers of alkyl vinyl ether and maleic acid or maleic anhydride monomers are mixed sodium and calcium salts of methyl vinyl ether and maleic anhydride having a specific viscosity of about 2.5 to 5.0 when measured at 25°C as a 1% w / v solution in methyl ethyl ketone (MEK) solution.

[0061] In another non-limiting embodiment, the present application provides a toothpaste-type composition comprising: (i) (a) at least one monovalent cation (M + ) and at least one divalent cation (M ++ or (b) (b1) 0.1 wt % to 20 wt % water-soluble salt of carboxymethyl cellulose (CMC) functionalized with at least one monovalent cation (M + ) and at least one divalent cation (M ++ (b2) a water-soluble salt of carboxymethylcellulose (CMC) functionalized with at least one monovalent cation (M + (ii) 0.1 wt% to 60 wt% of an orally acceptable solvent or carrier, including but not limited to water, glycerin, polyethylene glycol, polypropylene glycol, sorbitol, or combinations thereof, and (iii) 0.1 wt% to 20 wt% of a water soluble salt of carboxymethylcellulose (CMC) functionalized with, but not limited to, maleic anhydride, maleic acid, C 1 ~C 4(iii) 0.1 wt % to 20 wt % of an orally acceptable polymer of monomers comprising alkyl vinyl ether, alkylene oxide, alkyl lactam, triglyceride, animal or vegetable oil, or combinations thereof; and 0.1-80 wt % of further ingredients including an abrasive selected from the group including but not limited to calcium carbonate, calcium bicarbonate, silica, sodium carbonate, sodium bicarbonate and combinations thereof, a surfactant selected from the group including anionic, cationic, nonionic, zwitterionic surfactants and combinations thereof, an agent selected from fluoride providing compounds, zinc salts of organic and inorganic acids, flavors, foam enhancers, stabilizers, film forming polymers, peroxides, rheology modifiers, thickeners, salts, sweeteners, colorants, whitening agents, antibacterial agents, antiplaque agents, antitartar agents, biofilm formation inhibitors, antihypersensitivity agents, antigingivitis agents, mouthfeel modifiers, encapsulants and compounds, distortion relievers, stain inhibitors, vitamins and minerals, humectants, preservatives, dispersants, fixatives, pH adjusters and combinations thereof.

[0062] The one or more oral care active ingredients in the oral care compositions of the present disclosure may be selected from the group consisting of analgesics, antibacterial agents, anti-calculus agents, antibiotics, antioxidants, deodorants or breath fresheners, cooling agents, caffeine, drugs, desensitizing agents, dental remineralizing agents, enzymes, herbal medicines, drugs, minerals, peptides, pharmaceuticals, probiotics, preservatives, sensates, taste masking agents, spices, therapeutic agents, throat-soothing agents, vitamins, warming agents, and mixtures thereof.

[0063] Non-limiting examples of humectants can be or include glycerin, propylene glycol, and combinations thereof. Toothpaste-type compositions can include one or more whitening agents, but are not limited to hydrogen peroxide or one or more sources of hydrogen peroxide.

[0064] Non-limiting examples of antibacterial agents include zinc ion sources such as zinc acetate, zinc citrate, zinc gluconate, zinc glycinate, zinc oxide, zinc sulfate, and zinc sodium citrate, salts of phthalic acid such as phthalic acid and magnesium monopotassium phthalate, hexetidine, octenidine, sanguinarine, benzalkonium chloride, domiphen bromide, cetylpyridinium chloride (CPC) (including combinations of CPC with zinc and / or enzymes), alkylpyridinium chlorides such as tetradecylpyridinium chloride and N-tetradecyl-4-ethylpyridinium chloride, iodine, sulfonamides, alexazone, and the like. Antibacterial agents that may be used include bisbiguanides such as chlorhexidine, bisbiguanides such as diglycerides, piperidino derivatives such as delmopinol and octapinol, magnolia extract, grape seed extract, raspberry ketone, menthol, geraniol, citral, eucalyptol, eugenol, stannous fluoride, sodium monoclinic extract, herbal medicines, thymol, amoxicillin, tetracycline, doxycycline, minocycline, metronidazole, 4-isopropyl m-cresol (IPMP, o-cymen-5-ol) antibiotics such as neomycin, kanamycin, and clindamycin. A further exemplary list of useful antibacterial agents is provided in U.S. Patent No. 5,776,435 to Gaffar et al.

[0065] Non-limiting examples of antimicrobial agents include halogenated diphenyl ethers, 2,4,4-trichloro-2'-hydroxydiphenyl ether, 2,2-dihydroxy-5,5-dibromodiphenyl ether, 2,2-methylenebis-4(4-chloro-6-bromophenol), halogenated salicylanilides and halogenated carbanilides, stannous fluoride, zinc lactate, zinc citrate, zinc oxide.

[0066] Non-limiting examples of flavoring agents include flavors known to those skilled in the art, such as natural and artificial flavors. These flavoring agents are selected from synthetic flavor oils, flavoring aromatic compounds and / or aromatic oils, oleoresins, and extracts obtained from plants, leaves, flowers, fruits, and the like, and combinations thereof. Non-limiting representative flavor oils include spearmint oil, cinnamon oil, wintergreen oil (methyl salicylate), peppermint oil, clove oil, bay oil, anise oil, eucalyptus oil, thyme oil, cedar leaf oil, nutmeg oil, allspice, sage oil, mace, beater almond oil, and cassia oil. Further useful flavoring agents are artificial, natural, and synthetic fruit flavors, such as vanilla, and citrus oils, including lemon oil, orange oil, lime oil, grapefruit oil, and fruit essences, including apple, pear, peach, grape, blueberry, strawberry, raspberry, cherry, plum, pineapple, and apricot, and the like. These flavoring agents can be used in liquid or solid form and can be used individually or in admixture. Commonly used flavors include mints such as peppermint, menthol, spearmint, artificial vanilla, cinnamon derivatives, and various fruit flavors, whether used individually or in admixture.

[0067] Flavors can also provide breath freshening properties, especially mint flavors when used in combination with the cooling agents described herein below.Other useful flavors include aldehydes, esters and ketones, such as cinnamyl acetate, cinnamaldehyde, citral diethyl acetal, dihydrocarbyl acetate, eugenyl formate and raspberry ketone p-methyl amisole.In general, any flavor or food additive can be used, such as those described in Chemicals Used in Food Processing, Publication No. 1274, pages 63-258, by the National Academy of Sciences.This publication is incorporated herein by reference.This can include natural flavors and synthetic flavors.

[0068] Non-limiting examples of suitable animal and vegetable oils may include, but are not limited to, sunflower oil, corn oil, soybean oil, avocado oil, jojoba oil, pumpkin oil, grape seed oil, sesame seed oil, walnut oil, fish oil, glycerol tricaprocaprylate, purcellin oil, liquid jojoba oil, and blends thereof. Natural oils such as eucalyptus oil, lavender oil, vetiver oil, lily of the valley oil, lemon oil, sandalwood oil, rosemary oil, chamomile oil, savory oil, nutmeg oil, cinnamon oil, hyssop oil, caraway oil, orange oil, geranium oil, juniper oil, bergamot oil, and blends thereof are also suitable. There are five commonly available vegetable oils that contain more than 50% linoleic acid groups (in the form of glycerol esters). The oils in descending order of linoleic acid content are safflower oil (75%), sunflower oil (67.8%), corn oil (56%), cottonseed oil (55%) and soybean oil (52%).

[0069] Non-limiting examples of suitable vitamins or minerals may include vitamin A, vitamin C, vitamin D, vitamin E, vitamin K, vitamin B6, vitamin B12, thiamine, riboflavin, biotin, folic acid, niacin, pantothenic acid, sodium, potassium, calcium, magnesium, iron, copper, zinc, selenium, manganese, choline, chromium, molybdenum, cobalt, and combinations thereof.

[0070] Similarly, non-limiting examples of whitening agents that can be used in the oral care compositions include, but are not limited to, dyes, polyphosphates, phytic acid and salts of phytic acid, complex whitening agents or bleaching agents.Suitable whitening agents or whitening agents include peracids, peroxide compounds.Peroxides are believed to whiten teeth by releasing hydroxyl radicals that can break down plaque-stain complexes into a form that can be washed off or removed by abrasives.

[0071] Additionally, film-forming polymers may be included in the oral care composition. Suitable examples of such film-forming polymers may include, but are not limited to, synthetic anionic polymeric polycarboxylates (SAPPs), such as PVM / MA copolymers (Gantrez S-97, Ashland Inc.). Such polymers are also described in U.S. Pat. Nos. 5,334,375 and 5,505,933. SAPPs have previously been described as useful for relieving dentin hypersensitivity. Additionally, SAPPs have previously been described as antibacterial enhancers that improve the delivery of antibacterial agents to oral surfaces and enhance the retention of antibacterial agents on oral surfaces. It is fully contemplated by the present invention that film-forming polymers, such as PVM / MA copolymers, may be utilized in the compositions of the present invention as a means of reducing stain formation.

[0072] Non-limiting examples of sweetening agents may include, but are not limited to, sucrose, glucose, saccharin, dextrose, levulose, lactose, mannitol, sorbitol, fructose, maltose, xylitol, erythritol, saccharin salts, thaumatin, aspartame, D-tryptophan, dihydrochalcones, acesulfame, sucralose and cyclamate salts, particularly sodium cyclamate and sodium saccharin, and mixtures thereof.

[0073] The oral care composition according to the present disclosure may further comprise an abrasive. Non-limiting suitable examples of such abrasives may include silica abrasives, such as standard cleaning silica, heavy duty cleaning silica, or any other suitable abrasive silica. Further examples of abrasives that may be used in addition to or instead of silica abrasives include calcium phosphate abrasives, such as tricalcium phosphate (Ca 3 (PO 4 ) 2 ), hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2) or dicalcium phosphate dihydrate CaHPO 4 .2H 2 O or calcium pyrophosphate, calcium carbonate abrasives, or abrasives such as sodium metaphosphate, potassium metaphosphate, aluminum silicate, calcined alumina, bentonite or other siliceous materials or combinations thereof. The silica component of the silica-based material is an amorphous precipitated silica. Precipitated silicas include the following products available from JM Huber Corporation, Edison, NJ: Zeodent (登録商標) 103. Zeodent (登録商標) 113. Zeodent (登録商標) 114. Zeodent (登録商標) 115. Zeodent (登録商標) 118. Zeodent (登録商標) 119. Zeodent (登録商標) 165 and Zeodent (登録商標) 9175.

[0074] The oral care composition according to the present disclosure may further comprise a suitable anionic surfactant. Suitable examples of such surfactants may include, but are not limited to, water-soluble salts of alkyl sulfates having 8 to 20 carbon atoms in the alkyl radical (e.g., sodium alkyl sulfate) and water-soluble salts of sulfonated monoglycerides of fatty acids having 8 to 20 carbon atoms, such as sodium lauryl sulfate and sodium coconut monoglyceride sulfonate. Other suitable anionic surfactants are sarcosinates, such as sodium lauroyl sarcosinate, taurates, sodium lauryl sulfoacetate, sodium lauroyl isethionate, sodium lauryl carboxylate, and sodium dodecylbenzenesulfonate, and mixtures thereof. Other useful anionic surfactants include sarcosinate surfactants, isethionate surfactants, and taurate surfactants. The surfactants are the alkali metal or ammonium salts of these surfactants, sodium and potassium salts such as lauroyl sarcosinate, myristoyl sarcosinate, palmitoyl sarcosinate, stearyl sarcosinate, Amisoft CS-11 (amino acid and L-glutamic acid) and oleoyl sarcosinate.

[0075] Examples of suitable cationic surfactants are derivatives of aliphatic quaternary ammonium compounds with one long alkyl chain containing about 8 to 18 carbon atoms, such as lauryltrimethylammonium chloride, cetylpyridinium chloride, cetyltrimethylammonium bromide, diisobutylphenoxyethyldimethylbenzylammonium chloride, coconut alkyltrimethylammonium nitrite, cetylpyridinium fluoride, etc.

[0076] Examples of suitable nonionic surfactants may include, but are not limited to, Pluronics, polyethylene oxide condensates of alkylphenols, products resulting from the condensation of ethylene oxide with the reaction product of propylene oxide and ethylene diamine, ethylene oxide condensates of aliphatic alcohols, long chain tertiary amine oxides, long chain tertiary phosphine oxides, long chain dialkyl sulfoxides, and mixtures of the foregoing materials.

[0077] Examples of suitable zwitterionic surfactants can include, but are not limited to, derivatives of aliphatic quaternary ammonium, phosphonium and sulfonium compounds, where the aliphatic radical can be linear or branched, and one of the aliphatic substituents contains from about 8 to 18 carbon atoms and contains an anionic water solubilizing group, such as a carboxy, sulfonate, sulfate, phosphate or phosphonate group.

[0078] In another embodiment of the present disclosure, the oral care composition may further comprise a rheology modifier. Suitable examples of such thickeners include, as monomer units, water-soluble cellulose ethers such as, but not limited to, sodium carboxymethylcellulose, sodium carboxymethylhydroxyethylcellulose and hydroxyethylcellulose, vinylpyrrolidone polymers (N-vinylpyrrolidone, N-vinyl-2-pyrrolidone and N-vinyl-2-pyrrolidinone, also called polyvinylpyrrolidone). Other suitable thickeners include carboxyvinyl polymers (carbomers), carrageenan, laponite and other natural gums such as karaya gum, xanthan gum, guar gum, gum arabic and gum tragacanth. Colloidal magnesium aluminum silicate or micronized silica may be used as part of the thickener to further improve the texture. Other classes of thickeners or gelling agents include the class of homopolymers of acrylic acid crosslinked with alkyl ethers of pentaerythritol or alkyl ethers of sucrose. In various preferred embodiments, the carrier may include polyethylene glycol, ethylene oxide / propylene oxide, and silicone polymers and / or copolymers. When such copolymers / polymers are used, they may be selected from commercially available materials. Block copolymers of ethylene oxide propylene oxide are useful, but higher molecular weights, e.g., greater than 5000 Da, are preferred, such as PLURA CARE® L1220 (available from BASF, Wyandotte, Mich., USA). Low or medium molecular weight polyethylene glycols, e.g., PEG 400, PEG 600, PEG 800, PEG 1000, and mixtures thereof, are also useful. The carrier preferably provides a toothpaste with a viscosity of about 10,000 CPS to about 700,000 CPS, preferably about 30,000 CPS to about 300,000 CPS.

[0079] Non-limiting examples of "fluoride-supplying compounds" may include sodium fluoride, potassium fluoride, amine fluorides, ammonium fluoride, lead fluoride, manganese fluoride, copper fluorides such as copper(I) fluoride, zinc fluoride, barium fluoride, sodium fluorosilicate, ammonium fluorosilicate, sodium fluorozirconate, sodium monofluorophosphate, potassium fluorozirconate, sodium monofluorophosphate, aluminum monofluorophosphate and aluminum difluorophosphate and fluorinated sodium calcium pyrophosphate, tin fluoride such as tin(II) fluoride, tin(IV) fluoride or tin(II) chlorofluoride, and sodium hexafluorostannate.

[0080] Thus, toothpaste-type compositions are either aqueous or anhydrous compositions.

[0081] In another non-limiting embodiment, the present application provides a method for preparing a functionalized carboxymethyl cellulose, comprising: (i) at least one monovalent (M + ) a carboxymethylcellulose salt; and (ii) one or more divalent (M ++ ion exchange process involving reaction with a divalent (M ++ ) Salt, M ++ Chloride or M ++ Sulfate or M ++ carbonates, + M ++ to about 75:1 in the final functionalized CMC polymer.

[0082] In another non-limiting embodiment, the present application provides a monovalent cation-divalent cation (M + -M ++ (i) (a) a method for preparing M-carboxymethylcellulose comprising the steps of: ++ Chloride, M ++ Sulfate or M ++ Carbonates and (b) C 2 ~C 4(ii) preparing an aqueous solution of sodium carboxymethylcellulose (M + (iii) filtering the product of step (ii) to obtain a wet cake; (iv) stirring the wet cake of step (iii) in a hydroalcoholic solution for at least 30 minutes; and (v) repeating step (iv) at least three times to obtain M. + -M ++ (vi) drying the wet cake of step (v) at 50-70° C. for at least 15-30 minutes in a fluid bed dryer to obtain a dried M + -M ++ (vii) grinding the product of step (vi) to obtain carboxymethylcellulose; + -M ++ - isolating the dry powder of carboxymethyl cellulose.

[0083] M + -M ++ -Carboxymethylcellulose is calcium sodium carboxymethylcellulose. ++ Chloride, M ++ Sulfate or M ++ The carbonate is calcium chloride, calcium sulfate or calcium carbonate. 1 ~C 4 The alcohol is selected from methanol, ethanol, propanol, isopropanol and butanol. The milling step is carried out in a mill using a 0.75 mm screen, a 0.20 mm screen and a 0.08 mm screen. The dry powder has an average particle size in the range of 20 to 300 microns.

[0084] Thus, the present functionalized carboxymethyl cellulose has several unique features, namely: (i) at least one divalent cation (M ++) polyvalent cations including calcium, magnesium, zinc and stannous ions; (ii) low to medium molecular weight (2000-200,000 Daltons) or medium to high molecular weight (200,000-2,000,000 Daltons); (iii) highly soluble in water; and (iv) biodegradable, making them suitable for preparing mucoadhesive compositions, including applications in denture adhesives and toothpaste type formulations.

[0085] Further, certain aspects of the present application are described in detail by the following examples. Accordingly, all examples provided herein are to be construed as merely illustrative and not limiting the scope of the present invention in any way. EXAMPLES

[0086] At least one monovalent cation (M + ) and at least one divalent cation (M ++ The preparation and use of functionalized carboxymethylcellulose, which is directed to compositions containing high molecular weight carboxymethylcellulose functionalized with carboxymethylcellulose, and processes and methods for making mucoadhesive compositions, are illustrated in the examples below.

[0087] Example 1 Prototype Na + -Ca ++ -Synthesis of CMC polymer, XA-1517-050-1 4.35 grams of anhydrous calcium chloride was dissolved in 320 grams of deionized water with stirring over 30 minutes. 1,280 grams of methanol was added with continued stirring. 128 grams of Aqualon (sourced from Ashland Specialty Ingredients) was added with continued stirring. (商標)Carboxymethylcellulose, CMC 7H3SXF grade, was added to the above solution, resulting in a heterogeneous slurry. The mixture was stirred for 20 hours and then filtered to obtain a wet cake. The wet cake was dispersed in 1,600 grams of 80 / 20 by weight methanol / water, stirred for 30 minutes, and filtered again. This step was repeated two more times, followed by a final wash in 1,600 grams of neat methanol. The final material was dried at 65° C. using a fluid bed dryer until the total moisture content of the final product was below 5 weight percent.

[0088] Example 2 Prototype Na + -Ca ++ -Synthesis of CMC polymer, XA-1517-050-2 13.40 grams of anhydrous calcium chloride was dissolved in 320 grams of deionized water with stirring over 30 minutes. 1,280 grams of methanol was added with continued stirring. 128 grams of Aqualon (sourced from Ashland Specialty Ingredients) was added with continued stirring. (商標) Carboxymethylcellulose, CMC 7H3SXF grade, was added to the above solution, resulting in a heterogeneous slurry. The mixture was stirred for 20 hours and then filtered to obtain a wet cake. The wet cake was dispersed in 1,600 grams of 80 / 20 by weight methanol / water, stirred for 30 minutes, and filtered again. This step was repeated two more times, followed by a final wash in 1,600 grams of neat methanol. The final material was dried at 65° C. using a fluid bed dryer until the total moisture content of the final product was below 5 weight percent.

[0089] Example 3 Prototype Na + -Ca ++ -Synthesis of CMC polymer, XA-1517-078

[0090] 120.00 grams of anhydrous calcium chloride was dissolved in 800 grams of deionized water with stirring over 30 minutes. 800 grams of isopropanol was added with continued stirring. 180 grams of Aqualon (sourced from Ashland Specialty Ingredients) was added with continued stirring. (商標) Carboxymethylcellulose of CMC 7H3SXF grade was added to the above solution, resulting in a heterogeneous slurry. The mixture was stirred for 20 hours and then filtered to obtain a wet cake. The wet cake was dispersed in 1,600 grams of 80 / 20 by weight methanol / water, stirred for 30 minutes, and filtered again. This step was repeated two more times, followed by a final wash in 1,600 grams of neat methanol. The final material was dried at 65° C. using a fluid bed dryer until the total moisture content of the final product was below 5 weight percent. [Table 1]

[0091] Example 4 Prototype Na + -Mg ++ Synthesis of -CMC polymer (XA1517-018) In a 1.5 liter stainless steel reactor, 63.0 grams of cellulose (42.00 grams of Gaomi 2600 and 21.00 grams of NB421) were combined with 711.84 grams of isopropanol, 21.00 grams of deionized water, and 21.86 grams of magnesium chloride hexahydrate. The reactor was sealed, stirring was started using an overhead impeller, the reactor was cooled to 20° C., and oxygen was purged from the reactor by three vacuum / ultra-high purity nitrogen fills. Next, 95.39 grams of a 50% NaOH solution in deionized water was added, followed by two more fills of inert gas / ultra-high purity nitrogen. The mixture was stirred at 20° C. for 1 hour, after which 88.90 grams of a 50% monochloroacetic acid solution in isopropanol was added. The reactor was then heated to 70° C. for 30 minutes, held at 70° C. for 75 minutes, and cooled to 30° C. for 30 minutes. The final material was then removed from the reactor, filtered, and the resulting wet cake was washed in 800 grams of 80 / 20 by weight methanol / water for 30 minutes and neutralized to pH 7 using concentrated hydrochloric acid. The slurry was then filtered, and the resulting wet cake was subjected to another washing and neutralization step. A third wash was performed in the same solvent system, but this time without neutralization, and a final wash was performed in 800 grams of neat methanol. The final material was dried at 65° C. using a fluid bed dryer until the total moisture content of the final product was below 5 weight percent. The resulting dried material was milled using a Retsch mill to the desired particle size.

[0092] Example 5 Prototype Na + -Mg ++ Synthesis of -CMC polymer (XA1517-020) In a 1.5 liter stainless steel reactor, 63.0 grams of cellulose (42.00 grams of Gaomi 2600 and 21.00 grams of NB421) were combined with 711.84 grams of isopropanol and 49.68 grams of magnesium chloride hexahydrate. The reactor was sealed, stirring was started using an overhead impeller, the reactor was cooled to 20° C., and oxygen was purged from the reactor by three vacuum / ultra-high purity nitrogen fills. Next, 117.28 grams of a 50% NaOH solution in deionized water was added, followed by two more fills of inert gas / ultra-high purity nitrogen. The mixture was stirred at 20° C. for 1 hour, after which 88.90 grams of a 50% monochloroacetic acid solution in isopropanol was added. The reactor was then heated to 70° C. for 30 minutes, held at 70° C. for 75 minutes, and cooled to 30° C. for 30 minutes. The final material was then removed from the reactor, filtered, and the resulting wet cake was washed in 800 grams of 80 / 20 by weight methanol / water for 30 minutes and neutralized to pH 7 using concentrated hydrochloric acid. The slurry was then filtered, and the resulting wet cake was subjected to another washing and neutralization step. A third wash was performed in the same solvent system, but this time without neutralization, and a final wash was performed in 800 grams of neat methanol. The final material was dried at 65° C. using a fluid bed dryer until the total moisture content of the final product was below 5 weight percent. The resulting dried material was milled using a Retsch mill to the desired particle size. [Table 2]

[0093] Example 6 Prototype Na + -Zn ++ Synthesis of -CMC polymer (XA-1532-005) 73.00 grams of anhydrous zinc chloride was dissolved in 752.17 grams of deionized water over 30 minutes with stirring. 758.09 grams of isopropanol was added with continued stirring. 120 grams of Aqualon (sourced from Ashland Specialty Ingredients) was added with continued stirring. (商標)CMC 7H3SXF grade carboxymethylcellulose (XA1517-041, Table 1) was added to the above solution resulting in a heterogeneous slurry. The mixture was stirred for 20 hours and then filtered to obtain a wet cake. The wet cake was dispersed in 1025 grams of 70 / 30 w / w methanol / water, stirred for 30 minutes, and filtered again. This step was repeated two more times, followed by a final wash in 1025 grams of neat methanol. The final material was dried at 65° C. using a fluid bed dryer until the total water content of the final product was below 5 weight percent. Important polymer properties are shown in Table 3.

[0094] Example 7 Prototype Na + -Zn ++ Synthesis of -CMC polymer (XA1532-068) 35.30 grams of anhydrous zinc chloride was dissolved in 681.36 grams of deionized water with stirring over 30 minutes. 2779.66 grams of methanol was added with continued stirring. 275.00 grams of Aqualon (sourced from Ashland Specialty Ingredients) was added with continued stirring. (商標) CMC 7H3SXF grade carboxymethylcellulose (XA1517-041, Table 1) was added to the above solution resulting in a heterogeneous slurry. The mixture was stirred for 20 hours and then filtered to obtain a wet cake. The wet cake was dispersed in 2,350 grams of 70 / 30 w / w methanol / water, stirred for 30 minutes, and filtered again. This step was repeated two more times before a final wash in 2,350 grams of neat methanol was performed. The final material was dried at 65° C. using a fluid bed dryer until the total water content of the final product was below 5 weight percent. Important polymer properties are shown in Table 3. [Table 3]

[0095] Example 8 Preparation of denture adhesive type formulations A schematic method for preparing a standard denture fixative cream is described herein. The ingredients used and the amounts of these ingredients employed in formulating the various denture fixative type formulations are listed in Tables 4, 5 and 6. The denture fixative type creams were manufactured in batches of 25 grams. In a 100 ml plastic jar fitted with a screw cap, the required amount of petrolatum and mineral oil were charged into the plastic jar and melted by immersing the plastic jar in a well-mixed water bath maintained at 70-80°C until a clear homogenous liquid was obtained. The solid CMC polymer components were first added to the molten oil mixture according to the amounts mentioned in Tables 4, 5 and 6, gently mixed in and then homogenized by hand mixing. Poly(methyl vinyl ether / maleic acid)-poly(MVE / MA) (Gantrez) was then added to the molten oil mixture. (商標) MS-955, Ashland LLC.) Ca / Na mixed salt was added to the blend as per the amounts mentioned in Table 4, Table 5 and Table 6, gently mixed and then homogenized by hand mixing. Solid polymer was mixed and hand blended with oily mixture to obtain a smooth paste while maintaining the temperature of the mixture at 70-80°C by immersing the plastic jar in a suitable temperature controlled water bath. Finally, the denture fixative cream was subjected to high speed mixing in a Speed ​​Mixer DAC 400 FVZ machine from FlackTec Inc, Landrum, SC using centrifugal mode without blades. [Table 4] [Table 5] [Table 6]

[0096] Example 9 In vitro testing of denture adhesives Adhesion and relative thickness of the denture fixative films were recorded by a TA.XT Plus Texture Analyzer instrument from Stable Microsystems Texture Technologies Corp., fitted with a 50 Kg load cell and interfaced with Exponent software version 6.1.11.0 running on a PC. A custom-made Plexiglas probe-fixture assembly in the shape of a denture tooth was fitted to the Texture Analyzer instrument. Artificial saliva was injected between the walls of the Plexiglas probe-fixture assembly using a peristaltic pump. Real-time time-lapse images of the denture fixative creams being evaluated for adhesion performance by the Texture Analyzer instrument were recorded using a Canon EOS 5d Mark IV Digital SLR camera.

[0097] The prepared denture adhesive type formulation is hand mixed to a uniform, even cream consistency prior to each test. Three nearly identical strips of denture adhesive cream were weighed into a denture shaped cavity in the bottom plexiglass fixture on an analytical balance. The total mass of denture adhesive cream applied to the bottom fixture in each test was 2.0(+0.1)g. The bottom fixture was attached to the Texture Analyzer instrument and the top probe was lowered into the cavity of the bottom fixture, applying a precise compressive force of 4.5Kg while spreading the denture adhesive cream evenly to fill the bottom half of the cavity. The injection of artificial saliva was started. For the entire duration of the experiment, the denture adhesive cream remained submerged in contact with a thin layer of artificial saliva that was continuously replenished at a flow rate of 1ml / min. As soon as the denture adhesive cream layer was completely covered by the artificial saliva, the 7-hour test sequence was started. The adhesion force during chewing (in Newtons) and the thickness of the denture adhesive film between the top and bottom probes (in mm) were measured continuously throughout the experimental period. Each sample of the prepared denture adhesive type formulation was subjected to four successive experimental trials. The average plots of the four trials for each sample were compared for adhesion performance and thickness variability. The total adhesion of each sample was calculated as the area under the curve for the average plots of the four successive trials for each sample.

[0098] Example 10 In vivo adhesion results Figure 1 shows the results of the control denture adhesive and Na + -Mg ++Figure 2 shows the overlay of the average deposition profiles of denture adhesive type formulations containing -CMC (DA29-31). The deposition profile trace of each denture adhesive sample is the average of four consecutive experimental trials. Each overlay plot was divided into alternating phases consisting of slow chewing movements or rest phase (RP) and fast chewing movements or dynamic mastication (DM). The deposition force was recorded and reported in Newtons (N). Figure 2 shows the total deposition of each of the representative denture adhesive type formulations (control, DA29-31). Total deposition (in N) was measured as the total area under the curve for the average deposition profile trace of each of the representative denture adhesive type formulations.

[0099] 3, 5 and 7 show the results of the control denture adhesive and Na + -Ca ++ Figures 4, 6 and 8 show the overlay of the average deposition profile of denture adhesive type formulations containing -CMC (DA35-46). The deposition profile trace of each denture adhesive sample is the average of four consecutive experimental trials. Each overlay plot was divided into alternating phases consisting of slow chewing movements or rest phase (RP) and fast chewing movements or dynamic mastication (DM). The deposition force was recorded and reported in Newtons (N). Figures 4, 6 and 8 show the total deposition of each of the representative denture adhesive type formulations (control, DA35-46). Total deposition (in N) was measured as the total area under the curve for the average deposition profile trace of each of the representative denture adhesive type formulations.

[0100] 9 and 11 show the results of the control denture adhesive and Na + -Zn ++Figure 10 shows the average deposition profile overlays of denture fixative formulations containing -CMC (DA87-102). The deposition profile traces of each denture fixative sample are the average of four consecutive experimental trials. Each overlay plot was divided into alternating phases consisting of slow chewing movements or rest phase (RP) and fast chewing movements or dynamic mastication (DM). The deposition force was recorded and reported in Newtons (N). Figures 10 and 12 show the total deposition of each of the representative denture fixative formulations (control, DA87-102). Total deposition (in N) was measured as the total area under the curve for the average deposition profile traces of each of the representative denture fixative formulations. The total deposition caused by each of the prototypic denture fixative formulations tested by the in vitro method is shown in Table 7. [Table 7]

[0101] Example 11 Silica and Na + -Zn ++ -Toothpaste-type formulations containing CMC Charge an appropriately sized container with glycerin (1 wt% to 30 wt%) and divalent cation functionalized Na + -Zn ++ CMC (0.1wt%-6wt%) was thoroughly dispersed in glycerin using an overhead stirrer. A 70% solution of sorbitol (1wt%-30wt%) was then charged into the same vessel and thoroughly mixed using an overhead stirrer. Deionized water (1wt%-40wt%) was then added to the vessel and mixed vigorously with overhead stirring until a uniform viscous gel phase was obtained. A previously prepared aqueous solution of sodium fluoride (0.1wt%-0.3wt%) and sodium saccharin (0.1wt%-0.5wt%) was added to the vessel and mixed vigorously until a uniform viscous gel phase was obtained. The gel phase was transferred to the receptor jar of a suitable size whipping mixer and mixed with Zeodent 113 abrasive silica (1wt%-20wt%) and Zeodent 113 thickening silica (1wt%-20wt%). (登録商標)165 (0 wt%-10 wt%) was added to the gel phase and mixed into the gel phase by hand mixing. Titanium dioxide (0.1 wt%-2 wt%) was added to the mixture and gently mixed into the mixture by hand. The mixture was then high speed mixed under vacuum using a whipping mixer until a uniform paste was obtained. Finally, sodium lauryl sulfate surfactant (0.1 wt%-5 wt%) and flavors (0.1 wt%-5 wt%) were added to the paste and given a final high speed mix in the whipped mixture under vacuum to obtain the complete toothpaste type formulation.

[0102] Example 12 Calcium carbonate and Na + -Zn ++ -Toothpaste-type formulations containing CMC Charge an appropriately sized container with a 70% solution of sorbitol (1 wt% to 30 wt%) and divalent cation functionalized Na + -Zn ++ CMC (0.1wt%-6wt%) was thoroughly dispersed in the sorbitol solution using an overhead stirrer. Deionized water (1wt%-40wt%) was then added to the vessel and mixed vigorously with overhead stirring until a uniform viscous gel phase was obtained. Pre-prepared aqueous solutions of sodium monofluorophosphate (0.1wt%-2wt%), trisodium phosphate decahydrate (0.1wt%-2wt%) and sodium saccharin (0.1wt%-0.5wt%) were added to the vessel and mixed vigorously until uniform. The gel phase was transferred to the receptor jar of a suitable size whipping mixer and mixed with abrasive calcium carbonate (1wt%-50wt%) and thickening silica Zeodent. (登録商標)165 (0 wt%-10 wt%) is added to the gel phase and mixed into the gel phase by hand mixing. Titanium dioxide (0.1 wt%-2 wt%) is added to the mixture and gently mixed into the mixture by hand. The mixture is then high speed mixed under vacuum using a whipping mixer until a uniform paste is obtained. Finally, sodium lauryl sulfate surfactant (0.1 wt%-5 wt%) and flavors (0.1 wt%-5 wt%) are added to the paste and given a final high speed mix in the whipped mixture under vacuum to obtain the complete toothpaste type formulation.

[0103] The above description fully discloses the present invention, including the preferred embodiments thereof. Modifications and improvements of the embodiments expressly disclosed herein are within the scope of the following claims. Without further elaboration, it is believed that one skilled in the art can utilize the present invention to its fullest extent in light of the above description. The embodiments of the present invention in which an exclusive property or privilege is claimed are defined as follows:

Claims

1. At least one monovalent cation (M + ) and at least one divalent cation (M ++ ) Water-soluble salts of carboxylated polysaccharides functionalized with .

2. 2. The composition of claim 1, wherein the functionalized carboxylated polysaccharide is selected from the group consisting of carboxymethyl cellulose, carboxymethyl inulin, carboxymethyl guar, and carboxymethyl starch.

3. 10. The composition of claim 1, wherein the functionalized carboxylated polysaccharide is carboxymethyl cellulose.

4. At least one monovalent cation (M + ) and at least one divalent cation (M ++ ) Water-soluble salts of carboxymethylcellulose (CMC) functionalized with .

5. 5. The water-soluble salt of carboxymethylcellulose (CMC) according to claim 4, wherein the divalent cation is present in an amount of about 0.2 to 7.5 wt % based on the total CMC.

6. The water-soluble salt of carboxymethylcellulose (CMC) according to claim 4, wherein the monovalent cations and the divalent cations are present in the final functionalized CMC polymer in a weight ratio of 75:1 to 1:

75.

7. The water-soluble salt of carboxymethylcellulose (CMC) according to claim 4, wherein the carboxymethylcellulose (CMC) is optionally substituted with at least one monovalent cation (M + The water soluble salt is further combined with carboxymethyl cellulose (CMC) functionalized with .

8. 5. The water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, wherein the functionalized carboxymethyl cellulose (CMC) has a degree of substitution in the range of 0.4 to 1.

2.

9. 5. The water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, wherein the functionalized carboxymethyl cellulose (CMC) has a degree of substitution in the range of 0.4 to 0.

7.

10. 5. The water-soluble salt of carboxymethylcellulose (CMC) according to claim 4, wherein the functionalized carboxymethylcellulose has a weight average molecular weight in the range of 2000 to 2,000,000 Daltons.

11. 5. The water-soluble salt of carboxymethylcellulose (CMC) according to claim 4, wherein the functionalized carboxymethylcellulose has a weight average molecular weight in the range of 80,000 to 1,300,000 Daltons.

12. 5. The water-soluble salt of carboxymethylcellulose (CMC) according to claim 4, wherein the functionalized carboxymethylcellulose (CMC) maintains its inherent biodegradability.

13. 5. The water-soluble salt of carboxymethylcellulose (CMC) according to claim 4, wherein the functionalized carboxymethylcellulose has the structure (I): 【Chemistry 1】 CMCs functionalized with monovalent and divalent cations (In the formula, M + is a monovalent cation selected from the group consisting of sodium ions, potassium ions, and lithium ions; M ++ is a divalent cation selected from the group consisting of calcium, magnesium, zinc, tin and combinations thereof, n≧2 to n≦2000, and M + = 0.1 to 10 wt% and M ++ = 0.1 to 7.5 wt %.

14. 5. The water-soluble salt of carboxymethylcellulose (CMC) according to claim 4, wherein the functionalized carboxymethylcellulose has the structure (II): 【Chemistry 2】 CMC functionalized with monovalent cations (In the formula, M + is a monovalent cation selected from the group consisting of sodium ions, potassium ions and lithium ions, n≧2 to n≦2000, and M + = 0.1 to 10 wt %.

15. The water-soluble carboxymethyl cellulose (CMC) according to claim 4, wherein the monovalent cation (M + ) is selected from the group consisting of sodium, potassium and lithium.

16. The water-soluble carboxymethyl cellulose (CMC) according to claim 4, wherein the divalent cation (M ++ ) is selected from the group consisting of calcium, magnesium, zinc, tin and combinations thereof.

17. 5. The water-soluble carboxymethyl cellulose (CMC) of claim 4, wherein the functionalized carboxymethyl cellulose (CMC) is in dry powder form.

18. The water-soluble carboxymethyl cellulose (CMC) according to claim 4, wherein the functionalized carboxymethyl cellulose (CMC) is (i) Carboxymethylcellulose calcium sodium (Na + -Ca ++ - CMC), (ii) Sodium magnesium carboxymethylcellulose (Na + -Mg ++ - CMC), (iii) Sodium carboxymethylcellulose zinc (Na + -Zn ++ - CMC), (iv) Carboxymethylcellulose zinc calcium sodium (Na + -Ca ++ -Zn ++ - CMC), (v) Carboxymethylcellulose magnesium calcium sodium (Na + -Ca ++ -Mg ++ - CMC), (vi) Carboxymethylcellulose zinc magnesium sodium (Na + -Mg ++ -Zn ++ - CMC), (vii) Sodium carboxymethylcellulose tin (Na + -Sn ++ - CMC), (viii) Carboxymethylcellulose tin calcium sodium (Na + -Ca ++ -Sn ++ - CMC), (ix) Carboxymethylcellulose tin magnesium sodium (Na + -Mg ++ -Sn ++ -CMC) or (x) Carboxymethylcellulose tin zinc sodium (Na + -Zn ++ -Sn ++ - CMC) Water-soluble carboxymethylcellulose (CMC).

19. The water-soluble carboxymethylcellulose (CMC) according to claim 6, wherein the functionalized carboxymethylcellulose (CMC) is a conjugate of sodium carboxymethylcellulose and at least one functionalized carboxymethylcellulose (CMC) selected from the compounds according to (i) to (x) of claim 18, or a combination thereof.

20. The water-soluble carboxymethylcellulose (CMC) according to claim 6, wherein the functionalized carboxymethylcellulose (CMC) is carboxymethylcellulose calcium sodium (Na + -Ca ++ -CMC) or sodium carboxymethylcellulose magnesium (Na + -Mg ++ -CMC) or sodium carboxymethylcellulose zinc (Na + -Zn ++ -CMC), a water-soluble carboxymethylcellulose (CMC).

21. 7. The water-soluble carboxymethylcellulose (CMC) of claim 6, wherein the functionalized carboxymethylcellulose (CMC) comprises: (i) sodium carboxymethylcellulose (Na + -CMC), and (ii)(a) carboxymethylcellulose calcium sodium (Na + -Ca ++ -CMC) or (b) Carboxymethylcellulose magnesium sodium (Na + -Mg ++ -CMC) or (c) sodium carboxymethylcellulose zinc (Na + -Zn ++ Water-soluble carboxymethylcellulose (CMC), which is a conjugate with carboxymethylcellulose (CMC).

22. The water-soluble carboxymethyl cellulose (CMC) of claim 4, wherein the functionalized carboxymethyl cellulose (CMC) is used in oral care compositions, pharmaceutical compositions, home care compositions, industrial compositions, skin care compositions, food and dietary supplement compositions, coating compositions, and oil and energy industry compositions.

23. The water-soluble carboxymethylcellulose (CMC) of claim 4, wherein the functionalized carboxymethylcellulose (CMC) is used in an oral care composition selected from a mucoadhesive composition, a toothpaste / dentifrice type composition, an oral treatment composition, a mouthrinse composition and a denture adhesive type composition.

24. A mucoadhesive composition comprising: (i) (a) 0.1 wt % to 60 wt % of a water-soluble salt of the carboxymethyl cellulose (CMC) according to claim 4, or (b) a water-soluble salt of the carboxymethyl cellulose (CMC) of claim 4 and at least one monovalent cation (M + ) functionalized carboxymethyl cellulose (CMC) in a ratio of 0.1 wt % to 60 wt %; (ii) C of substantially alternating monomer structures 1 ~C 4 a maleic acid or maleic anhydride copolymer of 0.1 wt % to 60 wt % of an alkyl vinyl ether and maleic acid or maleic anhydride monomer, wherein 50 to 90 wt % of the acid moieties in the polymer have been converted to a metal salt or mixed salt; (iii) 0.1 wt % to 80 wt % of at least one further ingredient; 1. A mucoadhesive composition comprising:

25. 25. The mucoadhesive composition according to claim 24(i), wherein the functionalized water-soluble carboxymethylcellulose (CMC) has a degree of substitution in the range of 0.4 to 1.

2.

26. 25. The mucoadhesive composition according to claim 24(i), wherein the functionalized water-soluble carboxymethylcellulose (CMC) has a degree of substitution in the range of 0.4 to 0.

7.

27. The mucoadhesive composition of claim 24, wherein the functionalized carboxymethylcellulose has a weight average molecular weight in the range of 2000 to 1,500,000 Daltons.

28. 25. The mucoadhesive composition according to claim 24, comprising a substantially alternating monomer structure C 1 ~C 4 The maleic acid or maleic anhydride copolymer of an alkyl vinyl ether and a maleic acid or maleic anhydride monomer, wherein 50 to 90 wt % of the acid moieties in the polymer are substituted with at least one monovalent cation (M + ) and at least one divalent cation (M ++ 2. The maleic acid or maleic anhydride copolymer as defined above, converted into a salt or mixed salt of

29. 29. The mucoadhesive composition of claim 28, wherein the maleic acid or maleic anhydride copolymer is prepared by copolymerization of about 50 mole percent maleic acid or maleic anhydride and about 50 mole percent C at about 50-150° C. in the presence of a free radical initiator in a solvent or solvent-free process. 1 ~C 4 Maleic acid or maleic anhydride having a predetermined weight average molecular weight of about 500,000 to 3,000,000 and C produced by copolymerizing with an alkyl vinyl ether to produce a uniform fine powder substantially free of residual maleic anhydride. 1 ~C 4 A mucoadhesive composition comprising an alkyl vinyl ether.

30. 29. The mucoadhesive composition of claim 28, wherein the maleic acid or maleic anhydride and C 1 ~C 4 1. A mucoadhesive composition, wherein the alkyl vinyl ether is a methyl vinyl ether-maleic acid copolymer or a methyl vinyl ether-maleic anhydride copolymer having a number average molecular weight between about 50,000 and about 500,000, and about 50 to about 100 wt % of the carboxyl units in the polymer are converted to a mixture of metal salts selected from the group consisting of calcium, sodium, strontium, zinc, magnesium, iron, boron, aluminum, potassium, vanadium, chromium, manganese, nickel, copper, yttrium, titanium and mixtures thereof.

31. 30. The mucoadhesive composition according to claim 29, wherein the salt of methyl vinyl ether-maleic acid or methyl vinyl ether-maleic anhydride copolymer has a specific viscosity of about 2.5 to 5.0 when measured at 25°C as a 1% w / v solution in methyl ethyl ketone (MEK) solution.

32. 30. The mucoadhesive composition of claim 29, wherein the methyl vinyl ether-maleic acid or methyl vinyl ether-maleic anhydride copolymer or a salt of said copolymer comprises from about 18 to about 66 wt % of said mucoadhesive composition.

33. The mucoadhesive composition according to claim 29, wherein said methyl vinyl ether-maleic acid copolymer or methyl vinyl ether-maleic anhydride copolymer has a weight average molecular weight of about 700,000 to about 3,000,000.

34. 25. The mucoadhesive composition of claim 24, wherein the further ingredient is selected from the group consisting of abrasives, anti-caking agents, anti-fungal agents, anti-bacterial agents, anesthetic agents, antioxidants, antibiotics, anti-inflammatory agents, binders, buffers, colorants, cooling agents, dentin desensitizing agents, dispersing agents, enzymes, foaming agents, flavors, fillers, fragrances, gelling agents, humectants, hydrophobic carriers, hydrophilic oil-free ingredients, preservatives, pigments, plasticizers, analgesics, sweeteners, thickeners, viscosity modifiers, excipients, surfactants, stabilizers, sensates and mixtures thereof.

35. 25. The mucoadhesive composition according to claim 24, wherein said further ingredient is selected from petrolatum, mineral oil, olive oil, vegetable oil, silicon, glycerin, polyethylene glycol, propylene glycol, polypropylene glycol, poly(ethylene oxide-propylene oxide) copolymers, diethylene glycol, triethylene glycol, sorbitol, water and mixtures thereof.

36. 25. The mucoadhesive composition of claim 24, which is a buccal composition, an oral composition, a vaginal composition, a nasal composition, a rectal composition, an ophthalmic composition, a sublingual composition, a palatal composition or a denture adhesive type composition.

37. 25. The mucoadhesive composition of claim 24, formulated into an ointment, lotion, liquid, solid, semisolid, emulsion, powder, dispersion, gel, patch, aerosol or spray.

38. 1. A denture adhesive type composition comprising: (i) (a) 0.1 wt % to 60 wt % of a water-soluble salt of the carboxymethyl cellulose (CMC) according to claim 4, or (b) a water-soluble salt of the carboxymethyl cellulose (CMC) of claim 4 and at least one monovalent cation (M + ) functionalized carboxymethyl cellulose (CMC) in a ratio of 0.1 wt % to 60 wt %; (ii) C of substantially alternating monomer structures 1 ~C 4 a maleic acid or maleic anhydride copolymer of 0.1 wt % to 60 wt % of an alkyl vinyl ether and maleic acid or maleic anhydride monomer, wherein 50 to 90 wt % of the acid moieties in the polymer have been converted to a metal salt or mixed salt; (iii) 0.1 wt % to 80 wt % of at least one further ingredient; A denture adhesive type composition comprising:

39. 39. A denture fixative type composition according to claim 38, wherein the functionalized water-soluble carboxymethyl cellulose (CMC) has a degree of substitution in the range of 0.4 to 0.

7.

40. 39. A denture fixative type composition according to claim 38, wherein the functionalized water-soluble carboxymethyl cellulose (CMC) has a degree of substitution in the range of 0.4 to 1.

2.

41. 39. A denture fixative type composition according to claim 38, wherein the functionalized carboxymethylcellulose has a weight average molecular weight in the range of 2000 to 1,500,000 Daltons.

42. 39. A denture adhesive type composition according to claim 38, comprising: 1 ~C 4 1. A denture fixative type composition, wherein said maleic acid or maleic anhydride copolymer of alkyl vinyl ether and maleic acid or maleic anhydride monomer is a mixed sodium and calcium salt of methyl vinyl ether and maleic anhydride having a specific viscosity of about 2.5 to 5.0 when measured at 25° C. as a 1% w / v solution in methyl ethyl ketone (MEK) solution.

43. A toothpaste-type composition comprising: (i) (a) 0.1 wt % to 20 wt % of a water-soluble salt of the carboxymethyl cellulose (CMC) according to claim 4, or (b) a water-soluble salt of the carboxymethyl cellulose (CMC) of claim 4 and at least one monovalent cation (M + ) functionalized carboxymethyl cellulose (CMC) in a ratio of 0.1 wt % to 20 wt %; (ii) 0.1-60 wt % of an orally acceptable solvent or carrier selected from water, glycerin, sorbitol, propylene glycol, polypropylene glycol, PEG, ethylene oxide-propylene oxide polymers, or combinations thereof; (iii) including, but not limited to, maleic anhydride, maleic acid, C 1 ~C 4 0.1 wt % to 20 wt % of an orally acceptable polymer of monomers comprising alkyl vinyl ether, alkylene oxide, alkyl lactam, triglyceride, animal or vegetable oil, or combinations thereof; (iv) actives such as abrasives, anti-caking agents, fluoride delivering compounds, anti-fungals, anti-bacterials, anesthetics, antioxidants, anti-plaque agents, anti-tartar agents, biofilm inhibitors, anti-hypersensitivity agents, anti-gingivitis agents, antibiotics, anti-inflammatory agents, binders, buffers, colorants, cooling agents, fixing agents, desensitizing agents, dispersing agents, encapsulants, enzymes, foaming agents, flavors, fillers, fragrances, film forming polymers, gelling agents, humectants, hydrophobic carriers, hydrophilic oil free ingredients, 0.1 wt % to 80 wt % of at least one further ingredient selected from the group consisting of mouthfeel modifiers, minerals, preservatives, peroxides, salts, pigments, pH adjusters, plasticizers, analgesics, rheology modifiers, sweeteners, surfactants, stabilizers, sensates, distortion relievers, stain inhibitors, thickeners, viscosity modifiers, excipients, vitamins, whitening agents, vegetable and animal oils or combinations thereof, zinc salts of organic and inorganic acids or combinations thereof; 1. A toothpaste-type composition comprising:

44. 44. A toothpaste type composition according to claim 43, comprising (i) the thickening agent is (a) Water-soluble cellulose ethers such as sodium carboxymethylcellulose, sodium carboxymethylhydroxyethylcellulose, and hydroxyethylcellulose; (b) vinylpyrrolidone polymers such as N-vinylpyrrolidone, N-vinyl-2-pyrrolidone, N-vinyl-2-pyrrolidinone, and polyvinylpyrrolidone; (c) carboxyvinyl polymers (carbomers); (d) Carrageenan, laponite, and natural gums, such as karaya gum, xanthan gum, guar gum, gum arabic, and gum tragacanth; (e) Colloidal magnesium aluminium silicate, hydrated silica, thickening silica or micronised silica; (f) Homopolymers of acrylic acid crosslinked with alkyl ethers of pentaerythritol or with alkyl ethers of sucrose. is selected from the group consisting of (ii) the abrasive is selected from the group consisting of silica, calcium carbonate, calcium bicarbonate, sodium carbonate, and sodium bicarbonate; Toothpaste type composition.

45. Monovalent cations - divalent cations (M + -M ++ 2. A process for preparing carboxymethylcellulose comprising the steps of: (i) (a) M ++ Chloride, M ++ Sulfate or M ++ Carbonate and (b) C 2 ~C 4 preparing an aqueous solution of an alcohol; (ii) Sodium carboxymethylcellulose (M + ) to step (i) and stirring the product at ambient temperature for at least 30 minutes; (iii) filtering the product of step (ii) to obtain a wet cake; (iv) agitating the wet cake of step (iii) in a hydroalcoholic solution for at least 30 minutes; (v) Repeat step (iv) at least three times to obtain M + -M ++ - obtaining a pure wet cake of carboxymethyl cellulose; (vi) drying the wet cake of step (v) in a fluid bed dryer at 50-70° C. for at least 15-30 minutes to obtain a dried M + -M ++ obtaining carboxymethyl cellulose, (vii) grinding the product of step (vi) to obtain M + -M ++ - isolating the dry powder of carboxymethylcellulose; The method includes:

46. 46. ​​The method of claim 45, wherein the M + -M ++ The method, wherein the carboxymethylcellulose is calcium sodium carboxymethylcellulose.

47. 46. ​​The method of claim 45, wherein the M ++ Chloride, M ++ Sulfate or M ++ The process wherein the carbonate is calcium chloride, calcium sulfate or calcium carbonate.

48. 46. ​​The method of claim 45, wherein the C 1 ~C 4 The process wherein the alcohol is selected from methanol, ethanol, propanol, isopropanol and butanol.

49. 46. ​​The method of claim 45, wherein the grinding step is carried out using a 0.75 mm screen, a 0.20 mm screen, and a 0.08 mm screen.

50. 46. ​​The method of claim 45, wherein the dry powder has an average particle size in the range of 20 to 300 microns.

Citation Information

Patent Citations

  • Denture stabilizer

    US20050032940A1